Multiple Sclerozis and Pregnancy - Nebieridze, Pardis Tahery; Mirlohy, Sayed mohammad (Caucasus Journal of Health Sciences and Public Health, 2020)
Multiple sclerosis, a chronic neurological disease, has been proven to have an imbalance rate of incidence towards the female gender. As the onset age of the disease overlaps with the age of most pregnancies, concerns have arisen on the safety of the mother and the child, however, since not many pregnancies happen to be involved with MS, huge Cohort studies are needed to determine a certain fact regarding this issue.